Development of temperature-induced strains in coal–CH and coal–CO systems - Paweł Baran; Katarzyna Czerw; Natalia Czuma; Katarzyna Zarębska; Agnieszka Ćwik (Adsorption Science & Technology)
Expansion/contraction of coal, induced by the sorption of carbon dioxide and methane in isothermal and non-isothermal conditions, was measured. The investigation is of great importance in the context of validating the potential CO 2 sequestration in unmined coal seams. Changes in temperature in underground coal beds can influence the sorption balance, resulting in strains in coal strata, which could lead to the desorption of gas and leaks to the ground surface. The research shows that the strains induced by CO 2 sorption are about twice the size of those resulting from the sorption of CH 4 . The linear strains are anisotropic and greater in the direction perpendicular to the bedding plane. The results of the non-isothermal experiments show that a temperature increase gives rise to the sample swelling in the presence of methane, but a different pattern is observed for coal–CO 2 systems, where sample contraction occurs. This behaviour is explained by the different mechanism of CH 4 and CO 2 deposition and by the diversity in the maceral composition of the samples.